2006
DOI: 10.1007/s00296-006-0151-2
|View full text |Cite
|
Sign up to set email alerts
|

The reliability and validity of the Turkish version of the Western Ontario Rotator Cuff Index

Abstract: To adapt the Western Ontario Rotator Cuff (WORC) index for use in Turkey and to investigate its reliability and validity; the Turkish version of the WORC was developed according to the guidelines in the literature. Seventy-two patients with rotator cuff disease were administered the questionnaire and were also evaluated by using the University of California Los Angeles (UCLA) shoulder rating scale, Constant score, and Short Form (SF)-36 to test validity. The WORC questionnaire was repeated in 35 patients after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
61
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 23 publications
9
61
1
Order By: Relevance
“…The overall scale of the C-WORC and all the subscales had good or excellent internal consistency, which was consistent with other cross-culture adaptation studies and the original version (Cronbach’s alpha = 0.78–0.98) [10, 2026]. The overall scale of the C-WORC and all the subscales also showed good or excellent test-retest reliability.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The overall scale of the C-WORC and all the subscales had good or excellent internal consistency, which was consistent with other cross-culture adaptation studies and the original version (Cronbach’s alpha = 0.78–0.98) [10, 2026]. The overall scale of the C-WORC and all the subscales also showed good or excellent test-retest reliability.…”
Section: Discussionsupporting
confidence: 85%
“…In a systematic review on the patient-reported outcomes used for the evaluation of symptoms and functional limitations in individuals with RC disorders, it was concluded that the WORC is one of the most responsive questionnaires for this population [19]. The original version of the WORC was created in English and has been translated and validated into 7 languages, including German, Dutch, Brazil, and Japanese, among others [2026]. Unfortunately, a Chinese version has not yet been published even though China has the largest population of patients with RC disorders [27].…”
Section: Introductionmentioning
confidence: 99%
“…The functional assessments were carried out using the Turkish Version of the WORC index 16 and the ASES evaluation. 15 The shoulder index of the ASES consists of a pain score and a section of selfassessed ADL.…”
Section: Functional Assessmentmentioning
confidence: 99%
“…[16][17][18] A good correlation has been observed between the Constant score and the popular, disease-specific, patientevaluated Western Ontario Rotator Cuff (WORC) score. [19][20][21] The sensitivities (standardized response mean) of the 2 scores for the assessment of symptoms in patients with subacromial impingement or rotator cuff disease are comparable (slightly higher for the Constant score). 20 The aim of the present study was to investigate the relationship between clinical symptoms, as evaluated by the Constant score, and imaging criteria in patients with subacromial impingement syndrome without rotator cuff lesions.…”
Section: Introductionmentioning
confidence: 90%